Modeling anomalous diffusion from statistics to mathematics - Deng, Weihua; Xu, Pengbo; Hou, Ru 1990-; Wang, Wanli 1987- (New Jersey World Scientific, 2020)
One of the authors, Weihua Deng, has an interdisciplinary research background with a deep understanding on the related anomalous models from the viewpoint of mathematics and physics In this book, we not only introduce the widely investigated models but also discuss some new topics, for example, infinite densities, functionals, etc. This book will get more attention from undergraduates and some high-level students"--
Stochastic models -- Fokker-Planck equations -- Feynman-Kac equations -- Aging Fokker-Planck and Feynman-Kac equations -- Fokker-Planck and Feynman-Kac equations with multiple internal states -- Fractional reaction diffusion equations and corresponding Feynman-Kac equations -- Renewal theory for fractional Poisson process : typical versus rare -- Governing equation for average first passage time and transitions among anomalous diffusions.
Includes bibliographical references and index.
Keywords: Differential equations, Partial; Stochastic processes; Diffusion -- Mathematical models